Proyecto de elaboración de un plan de negocio para la producción y comercialización del morocho de plátano como snack - Vargas Pérez, Guido E. (2010)
This project is a business plan that implements the micro Procompla (Producer and marketer of bananas), the same that produces and markets natural snack product and native of the peninsular region, as is the Banana Morocho. Procompla has developed a market study, the same meeting the mark implementation of good manufacturing practices and provides for investment return expectations. Besides contributing to the productive activity of traditional and indigenous peninsular not disappear, but rather i economic alternative to generate employment, undertook a market study, a technical and financial feasibility, which guarantee favorable results viability and sustainability of the business. The business plan set determines a Feasibility viable, b investment in the first year, making the projection to 5 years, the business will have a tendency to keep increasing each year, but began to consolidate to receive profits and therefore the equity is strengthened.